PENGARUH STORE ATMOSPHERE, INOVASI PRODUK DAN CUSTOMER EXPERIENCE TERHADAP KEPUASAN PELANGGAN CAFE WARUNK UPNORMAL DI BANJARMASIN KALIMANTAN SELATAN - Mukti, Waluyo; Maryono, Maryono; Hidayati, Noor (Bisnis Smart, 2020)
This study aims to determine the effect of Store Atmosphere, Product Innovation and Customer Experience on Cafe Warunk UpNormal Customer Satisfaction in Banajarmasin. This research uses a quantitative approach in the form of explanatory. The sample in this study is Warunk UpNormal customers with 155 respondents with the sampling technique using simple random sampling. Data collection techniques using questionnaires and data analysis using multiple linear regression analysis. The test results prove that there is no partial significant effect of Store Atmosphere (X1) on Customer Satisfaction sig value of ? 0.05 and calculated t value of 0.920 and There is a significant effect partially Product Innovation (X2) on Customer Satisfaction because the sig value is 0,000 <0 , 05 and the value of t count 3.131 and also there is a partially significant effect of Customer Experience (X3) on Customer Satisfaction because the sig value is 0,000 <0,05 and the value of t is 4,791. The test together shows that there is a simultaneous significant effect of Store Atmosphere (X1) and Product Innovation (X2) and Customer Experience (X3) on Customer Satisfaction (Y) because the sig value is 0,000 <0,05 and the calculated F value is 40,489.